KRITIK TEOLOGIS IMAM JALALUDDIN AS-SUYUTHI TERHADAP TAFSIR AL-ZAMAKHSYARI - Imanuddin (LPPM Institut Daarul Qur'an Jakarta, Indonesia, 2024)
This article examines the critique of Imam Jalaluddin As-Suyuthi regarding several theological issues in Al-Zamakhsyari's exegesis. This critique is found in his Hashiyah al-Baidhawi and focuses on the theological differences between the Ash'ari and Mu'tazilah schools of thought in interpreting Quranic verses related to theological matters. Al-Zamakhsyari, as a prominent Mu'tazilah figure, presents differing views in his exegesis Al-Kashshaf, which has sparked theological debates within the Islamic world. This research uses a library research method, analyzing classical and modern texts related to the exegesis of As-Suyuthi and Al-Zamakhsyari. A critical analysis approach is employed to explore As-Suyuthi's arguments in responding to Mu'tazilah views and their impact on Islamic religious understanding. The research findings indicate that As-Suyuthi's critique provides a strong theological foundation for the Ash'ari school and plays a crucial role in reinforcing the importance of an interpretation of the Quran that aligns with the correct theological stance. Furthermore, the critique emphasizes that As-Suyuthi not only focuses on correcting the views of others but also seeks to redefine how the Quran should be interpreted within the framework of authentic belief, thus clarifying the epistemological position of Ash'ariyah in relation to Mu'tazilah thought.